In-Country programme on Training needs Assessnent 31 Januari - 11 Februari 2000 Yogyakarta, Indonesia - Indonesia. Directorate of Technical and Vocational Education Ministry of Education. (Directorate of Technical and Vocational Education Ministry of Education, 2000)
iii, 56 p. : il.; 29 cm.